2019
DOI: 10.18488/journal.aefr.2019.93.389.401
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Risks on the Stability of Tunisian Conventional Banks

Abstract: This paper examines the impact of credit risk, liquidity risk, and operational risk on Tunisian bank stability. These major risks continue to threaten Tunisian banks which are still developing traditional activities, despite the exhaustion of the main factors that have long sustained banking intermediation. To do this, we used data from all conventional banks operational during the period 2005-2015 and we used panel data analysis. Empirical results show that the stability of banks is closely linked to factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
2
11
2
1
Order By: Relevance
“…The study used 180 observations from 15 banks in Pakistan. The mean value of the z-score (which represents the banks' stability) is very low as compared to values reported in the literature from different countries, like Adusei (2015) reported 2.29 the value of the z-score of Ghana banks while (Zaghdoudi, 2019) reported 20.87 for Tunisian banks, which is very high and shows the stability of banks. Our value of 0.9161 revealed that our banks are less stable.…”
Section: Estimation Procedurescontrasting
confidence: 52%
See 2 more Smart Citations
“…The study used 180 observations from 15 banks in Pakistan. The mean value of the z-score (which represents the banks' stability) is very low as compared to values reported in the literature from different countries, like Adusei (2015) reported 2.29 the value of the z-score of Ghana banks while (Zaghdoudi, 2019) reported 20.87 for Tunisian banks, which is very high and shows the stability of banks. Our value of 0.9161 revealed that our banks are less stable.…”
Section: Estimation Procedurescontrasting
confidence: 52%
“…Among these, many studies revealed that credit risk reduces the banks' stability (Acharya and Mora, 2013;Rajhi and Hassairi, 2013;Khemais, 2019;Djebali and Zaghdoudi, 2020). Besides these, many studies find no significant influence of credit risk on banks' stability (Amara and Mabrouki, 2019;Zaghdoudi, 2019). Based on the above discussion, we hypothesized:…”
Section: Credit Risk and Financial Stabilitymentioning
confidence: 90%
See 1 more Smart Citation
“…A further research by Ghenimi et al (2017) proved that bank size has a positive and significant effect on credit risk. In addition, according to Zaghdoudi (2019) and Ghenimi et al (2017), bank size also had a negative and significant effect on bank stability. H 8 : Bank size affects liquidity risk.…”
Section: Bank Sizementioning
confidence: 96%
“…Setiawan and Widiastuti (2019) examined the effect of credit risk and liquidity risk individually or simultaneously on bank stability in Indonesia; 5. Zaghdoudi (2019) examined the effect of credit risk, liquidity risk, and operational risk on bank stability in Tunisia; 6. Djebali and Zaghdoudi (2020) examined the effect of the threshold effect of liquidity risk and credit risk on bank stability in the MENA region.…”
Section: Effect Of Liquidity Risk and Credit Risk On Bank Stabilitymentioning
confidence: 99%